Status and distribution of jaguarundi in Texas and Northeastern México: Making the case for extirpation and initiation of recovery in the United States. Issue 3 (21st March 2022) - Lombardi, Jason V.; Haines, Aaron M.; Watts, G. Wesley; Grassman, Lonnie I.; Janečka, Jan E.; Caso, Arturo; Carvajal, Sasha; Wardle, Zachary M.; Yamashita, Thomas J.; Stasey, W. Chad; Branney, Aidan B.; Scognamillo, Daniel G.; et al.
Abstract: The jaguarundi ( Puma yagouaroundi) is a small felid with a historical range from central Argentina through southern Texas. Information on the current distribution of this reclusive species is needed to inform recovery strategies in the United States where its last record was in 1986 in Texas. From 2003 to 2021, we conducted camera‐trap surveys across southern Texas and northern Tamaulipas, México to survey for medium‐sized wild cats (i.e., ocelots [ Leopardus pardalis ], bobcats [ Lynx rufus ], and jaguarundi). After 350, 366 trap nights at 685 camera sites, we did not detect jaguarundis at 16 properties or along 2 highways (1050 km 2 ) in Texas. However, we recorded 126 jaguarundi photographic detections in 15, 784 trap nights on 2 properties (125.3 km 2 ) in the northern Sierra of Tamaulipas, Tamaulipas, México. On these properties, latency to detection was 72 trap nights, with a 0.05 probability of detection per day and 0.73 photographic event rate every 100 trap nights. Due to a lack of confirmed class I sightings (e.g., specimen, photograph) in the 18 years of this study, and no other class I observations since 1986 in the United States, we conclude that the jaguarundi is likely extirpated from the United States. Based on survey effort and results from México, we would have expected to detect jaguarundis over the course of the study if still extant in Texas. We recommend that state and federal agencies consider jaguarundis as extirpated from the United States and initiate recovery actions as mandated in the federal jaguarundi recovery plan. These recovery actions include identification of suitable habitat in Texas, identification of robust populations in México, and re‐introduction of the jaguarundi to Texas. Abstract : From 2003 to 2021, we conducted camera‐trap surveys across southern Texas and northern Tamaulipas, México to survey for wild cats (i.e., jaguarundi, ocelots, bobcats). After 350, 366 trap nights at 685 camera sites, we failed to detect jaguarundis at 16 properties and along 2 highways (1050 km 2 ) in Texas, but had 126 detections in Mexico. Due to a lack of confirmed class I sightings (e.g., specimen, photograph) in the 18 years of this study, and no other class I observations or roadkill since 1986, we conclude that the jaguarundi is likely extirpated from the United States.